2014
DOI: 10.1111/ejn.12526
|View full text |Cite
|
Sign up to set email alerts
|

Distinct axo‐somato‐dendritic distributions of three potassium channels in CA1 hippocampal pyramidal cells

Abstract: Potassium channels comprise the most diverse family of ion channels and play critical roles in a large variety of physiological and pathological processes. In addition to their molecular diversity, variations in their distributions and densities on the axo-somato-dendritic surface of neurons are key parameters in determining their functional impact. Despite extensive electrophysiological and anatomical investigations, the exact location and densities of most K+ channels in small subcellular compartments are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 66 publications
3
47
1
Order By: Relevance
“…There are now a number of subunit-specific antibodies that can be used to identify and map the cellular and subcellular localization patterns of GIRK channel subunits in the CNS. Some of these antibodies have been validated using GIRK knockout mice, confirming the specificity of the immunolabeling patterns using different techniques (Aguado et al, , 2013Booker et al, 2013;Ciruela et al, 2010;Fernández-Alacid et al, 2009Kirizs, Kerti-Szigeti, Lorincz, & Nusser, 2014;Koyrakh et al, 2005;Kulik et al, 2006). Four high-resolution immunohistochemical techniques have been developed and successfully used for the subcellular distribution of GIRK channels: (i) preembedding immunoperoxidase (Drake, Bausch, Milner, & Chavkin, 1997;Fernández-Alacid et al, 2009;Ponce et al, 1996), (ii) preembedding immunogold Booker et al, 2013;Ciruela et al, 2010;Fernández-Alacid et al, 2009Koyrakh et al, 2005;Kulik et al, 2006;Labouebe et al, 2007;Marker, Luján, Loh, & Wickman, 2005), (iii) postembedding immunogold Fernández-Alacid et al, 2009Koyrakh et al, 2005;Marker et al, 2005), and (iv) the sodium dodecyl sulfate (SDS)-digested freeze-fracture replica labeling (SDS-FRL; Kirizs et al, 2014;Kulik et al, 2006) methods, which have revealed that GIRK channel subunits are localized with extraordinary precision in defined subcellular compartments of neurons in the CNS (Fig.…”
Section: Neuroanatomical Approaches To the Study Of Girk Channel Distmentioning
confidence: 75%
See 2 more Smart Citations
“…There are now a number of subunit-specific antibodies that can be used to identify and map the cellular and subcellular localization patterns of GIRK channel subunits in the CNS. Some of these antibodies have been validated using GIRK knockout mice, confirming the specificity of the immunolabeling patterns using different techniques (Aguado et al, , 2013Booker et al, 2013;Ciruela et al, 2010;Fernández-Alacid et al, 2009Kirizs, Kerti-Szigeti, Lorincz, & Nusser, 2014;Koyrakh et al, 2005;Kulik et al, 2006). Four high-resolution immunohistochemical techniques have been developed and successfully used for the subcellular distribution of GIRK channels: (i) preembedding immunoperoxidase (Drake, Bausch, Milner, & Chavkin, 1997;Fernández-Alacid et al, 2009;Ponce et al, 1996), (ii) preembedding immunogold Booker et al, 2013;Ciruela et al, 2010;Fernández-Alacid et al, 2009Koyrakh et al, 2005;Kulik et al, 2006;Labouebe et al, 2007;Marker, Luján, Loh, & Wickman, 2005), (iii) postembedding immunogold Fernández-Alacid et al, 2009Koyrakh et al, 2005;Marker et al, 2005), and (iv) the sodium dodecyl sulfate (SDS)-digested freeze-fracture replica labeling (SDS-FRL; Kirizs et al, 2014;Kulik et al, 2006) methods, which have revealed that GIRK channel subunits are localized with extraordinary precision in defined subcellular compartments of neurons in the CNS (Fig.…”
Section: Neuroanatomical Approaches To the Study Of Girk Channel Distmentioning
confidence: 75%
“…In the hippocampus, GIRK1, GIRK2, and GIRK3 are strongly expressed in CA1-CA3 pyramidal neurons and in dentate gyrus granule cells with overlapping distribution patterns, as assessed by in situ hybridization (Chen et al, 1997;Karschin et al, 1996;Karschin & Karschin, 1997;Kobayashi et al, 1995;Saenz del Burgo et al, 2008) and immunohistochemical studies (Fernández-Alacid et al, 2011;Kirizs et al, 2014;Koyrakh et al, 2005;Kulik et al, 2006;Saenz del Burgo et al, 2008;Fig. 3C-E).…”
Section: Distribution Of Girk1 Girk2 and Girk3 Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biophysical properties of the current are strongly influenced by both the subunit composition of the tetramers and the presence of ancillary subunits. A recent study using electron microscopy coupled to freeze-fracture replica immunolabeling technique indicates that Kv1.1 channels are located on the axon initial segment (AIS) and the presynaptic terminals in the CA1 region [23]. These channels are blocked by 4-aminopyridine or by dendrotoxin, a toxin from the venom of the mamba snake (dendroaspis).…”
Section: Adf Resulting From Inactivation Of Presynaptic Kv1 Channelsmentioning
confidence: 99%
“…The presence of these channels, with their signature characteristics and expression profiles, has been shown to play critical roles in the physiology, plasticity and pathophysiology of hippocampal neurons and their networks. Therefore, it is essential that the biophysical properties and expression profiles of these channels be tightly regulated to ensure functional robustness Bittner et al, 2012;Brager and Johnston, 2014;Johnston, 2004, 2005;Colbert and Johnston, 1996;Colbert et al, 1997;Dingledine et al, 1999;Gasparini and Magee, 2002;Hoffman et al, 1997;Hu et al, 2007;Johnston et al, 2003;Johnston et al, 2016;Johnston et al, 1996;Johnston and Narayanan, 2008;Kerti et al, 2012;Kirizs et al, 2014;Kullmann, 2002;Lai and Jan, 2006;Lerche et al, 2013;Lorincz et al, 2002;Lorincz and Nusser, 2010;Magee, 1998;Magee and Cook, 2000;Magee and Johnston, 1995;Migliore and Shepherd, 2002;Narayanan and Johnston, 2012;Nusser, 2009Nusser, , 2012Nusser et al, 2007;Paoletti et al, 2013;Shah et al, 2010;Sjostrom et al, 2008;Terzic and Perez-Terzic, 2010;Vacher et al, 2008).…”
Section: Degeneracy In the Properties Of Channels And Receptorsmentioning
confidence: 99%